The availability of Arabic calligraphy skills for sixth graders of basic education from the point of view of their teachers - Bin Ali, Radhwan Adnan Ali (Journal of Curriculum and Teaching Methodology, 2022)
The study aimed to find out the availability of Arabic calligraphy skills for sixth graders of basic education from the point of view of their teachers. To achieve the goal of the study, the descriptive approach used the survey analysis, and a questionnaire was prepared to collect data consisting of (20) items, which were divided into three areas: the domain of general skills that included (8) items, and the domain of accompanying skills during teaching Arabic calligraphy that included (5) items, The field of written performance included (7) paragraphs, and the research sample consisted of (40) teachers of the Arabic language who practice the teaching process in the capital Sana’a, they were chosen by random method. Through the results of the questionnaire, it was found that the skills of Arabic calligraphy are available to the sixth grade students of the basic education stage, except for some skills in which there are weaknesses. Arabic to teachers with written skills.
Keywords: Arabic Language; Writing; Calligraphy